Pengaruh Perceived Quality dan Perceived Value of Cost terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan pada Fresh.Co - Auryn Aprillia Chandrawati; Deandra Vidyanata (JEMBATAN, 2022)
This study aims to identify the significant influence of Perceived Quality and Perceived Value of Cost to Customer Loyalty through Customer Satisfaction on Fresh.co using quantitative research methodology. The results of the study indicate that there is a positive and insignificant influence between Perceived Quality and Customer Loyalty, a positive and significant influence between Perceived Value of Cost and Customer Loyalty, a positive and significant influence between Perceived Quality and Customer Satisfaction, a positive and significant influence between Perceived Value of Cost and Customer Loyalty, a positive and significant influence between Customer Satisfaction and Customer Loyalty. Meanwhile, Customer Satisfaction mediates fully and significantly the relation between Perceived Quality and Customer Loyalty. Customer Satisfaction also mediates partially and significantly the relation between Perceived Value of Cost and Customer Loyalty.